Exploring Single-Electron Transistors (SETs) in Molecular Electronics: Advanced Simulations Using TCAD and Virtuoso Framework - Anil Kumar (Innovative Research Thoughts, 2017)
Molecular electronics, leveraging the unique properties of molecules as fundamental building blocks, holds significant potential for the future of nanoelectronics. This research focuses on the simulation and analysis of single-electron transistors (SETs), employing advanced techniques such as Technology Computer Aided Design (TCAD) and the Virtuoso framework. We explore the intricacies of device layout, electron wavefunction coupling effects, and the impact of electrostatic coupling. Additionally, the study delves into the quantum mechanical effects, discretization of current, and the challenges associated with single-electron devices. The results underscore the importance of precise fabrication methods and innovative approaches to enhance the performance of SETs. The findings demonstrate the potential applications and limitations of SETs, highlighting their relevance in the realm of molecular electronics.